PROGRESS REPORT ON THE DEVELOPMENT OF THE GENERAL SCIENCE CURRICULUM PROGRAM IN THE PUBLIC SCHOOLS OF NEW YORK CITY. - Beck, Alfred D. (Science Education, 1956)
The article focuses on the development of the general science curriculum program of public schools in New York City. The planned new course of study provides two units for the 7th grade, three units for the 8th grade and five units for the 9th grade and is considered as a major subject for pupils. Through the general science curriculum program, pupil-teacher ratio is reduced in a sense that both teachers and pupils have fewer personalities to deal with at a particular time, preparations a teacher must take during a week is lessened and the number of notebooks and tests a teacher has to rate and number of marks he has to record is also reduced.